Shaping Crisis Perceptions: Nostalgia and Political Ideological Threats in the 2020 US Election - Simion, Luciana; Bligh, Michelle; Kohles, Jeffrey; Martin, Daniel (Journal of Organizational Psychology, 2025)
This study investigates the role of nostalgia in shaping ideological and psychological threat perception and its impact on crisis evaluations during the 2020 U.S. presidential election. Specifically, it explores how collective nostalgia predicts the perceived severity of threats to conservative and progressive ideologies and how these perceptions influence the broader understanding of a multidimensional crisis. Results indicate that nostalgia significantly heightens perceived threats to conservative ideologies, intensifying voters’ crisis perceptions. By examining the interplay between nostalgia, political ideology, and crisis perception, this research offers valuable insights into voter behavior and organizational responses during periods of socio-political upheaval.